Harmonic stability analysis of multi-paralleled 3-phase PV inverters tied to grid - R. S. Ravi Sankar; K. K. Deepika; A. V. Satyanarayana (Institute of Advanced Engineering and Science, 2021)
In this paper the harmonic stability is investigated for multi paralleled three-phase photovoltaic inverters connected to grid. The causes to harmonically stabilize/destabilize the multi-paralleled PV inverters when tied to the grid isanalysed by the impedance-based stability criterion (IBSC). In this paper stability of the system is investigated by varying the grid inductance with constant grid resistance and also by varying load impedance while maintaining grid inductance constant. Stability of the multiple three phase inverters tied to the grid with different grid impedance, inductance value inparticular are analyzed. Overall system is stable up to grid inductance of5mH even though there is change in load admittance. It is concluded that system stability depends only on grid impedance. It is verified with Matlab Simulations.